PENGEMBANGAN DAN IMPLEMENTASI SISTEM KEAMANAN BERBASIS IOT UNTUK PEMANTAUAN MURID TAMAN KANAK - KANAK PERSPEKTIF ONTOLOGI, EPISTEMOLOGI, DAN HEURISTIK - Yesputra, Rolly (Smart Education, 2025)
Abstract: The advancement of the Internet of Things (IoT) and Radio Frequency Identification (RFID) technologies offers significant opportunities to enhance security in educational environments, particularly at the kindergarten level. This research aims to develop and implement an IoT-based security system that leverages RFID technology to monitor students in real time. The system is designed to provide quick and accurate information to parents and schools regarding the movement and location of students, especially in emergencies or security threats. This study adopts three philosophical perspectives: ontology, epistemology, and heuristics. The ontological perspective examines the existence of students as digital entities represented by RFID data connected to the IoT network. The epistemological perspective focuses on the reliability and validity of the data in accurately and consistently determining students’ locations, including an analysis of technical limitations such as signal interference and RFID reading errors. The heuristic perspective evaluates the decision-making process during system development, including feedback-based iterations from end users to improve system efficiency and effectiveness. The research findings indicate that the developed system is capable of providing real-time student monitoring with a high degree of accuracy, as well as enhancing parents’ and schools’ confidence in student safety. This philosophical approach provides in-depth insights into the role of technology in education and child safety, as well as how technology can be effectively integrated into modern educational environments. Keywords: IoT, Student Security System, Ontology, Epistemology, Heuristics Abstrak: Perkembangan teknologi Internet of Things (IoT) dan Radio Frequency Identification (RFID) membuka peluang signifikan dalam meningkatkan keamanan di lingkungan pendidikan, khususnya pada tingkat taman kanak-kanak. Penelitian ini bertujuan untuk mengembangkan dan menerapkan sistem keamanan berbasis IoT yang memanfaatkan teknologi RFID guna memantau siswa secara real-time. Sistem ini dirancang untuk memberikan informasi yang cepat dan akurat kepada orang tua dan pihak sekolah terkait pergerakan dan lokasi siswa, terutama dalam situasi darurat atau ancaman keamanan. Pendekatan penelitian ini mencakup tiga perspektif filosofis: ontologi, epistemologi, dan heuristik. Perspektif ontologis mengkaji keberadaan siswa sebagai entitas digital yang diwakili oleh data RFID yang terhubung ke jaringan IoT. Perspektif epistemologis berfokus pada keandalan dan validitas data dalam menentukan lokasi siswa secara akurat dan konsisten, termasuk analisis keterbatasan teknis seperti gangguan sinyal dan kesalahan pembacaan RFID. Perspektif heuristik mengevaluasi proses pengambilan keputusan selama pengembangan sistem, termasuk iterasi berbasis umpan balik dari pengguna akhir untuk meningkatkan efisiensi dan efektivitas sistem. Hasil penelitian menunjukkan bahwa sistem yang dikembangkan mampu memberikan pemantauan siswa secara real-time dengan tingkat akurasi tinggi, serta meningkatkan kepercayaan orang tua dan pihak sekolah terhadap keselamatan siswa. Pendekatan filosofis ini memberikan wawasan mendalam tentang peran teknologi dalam pendidikan dan keamanan anak, serta bagaimana teknologi dapat diintegrasikan secara efektif dalam lingkungan pendidikan modern..Kata kunci: IoT, Sistem Keamanan Siswa, Ontologi, Epistemologi, Heuristika.